Microwave-assisted melamine-based polyaminals and their application for metal cations adsorption. (15th July 2021) - Sandín, Ricardo; González-Lucas, Maria; Sobarzo, Patricio A.; Terraza, Claudio A.; Maya, Eva M.
Graphical abstract: Highlights: Three new polyaminals (PAs) from melamine were prepared by microwave irradiation. PAs showed high N content and great stability but different porous properties. PAs exhibited good adsorptions capacities for divalent cations at pH 5. PA containing pyridine rings exhibited the best adsorption capacity of the series. Two PAs could compete with some of the commercial ion exchange resins. Abstract: Three new cross-linked melamine-based polyaminal networks containing phenyl (MA-iPh ), pyridine (MA-Py ) or thiophene (MA-Th ) moieties were easily prepared by microwave irradiation (MW) in shorter reaction times (between 1.5 and 4 h) than conventional heating (72 h). The networks showed high nitrogen content (27–37%), specific surfaces between 34 and 424 m 2 g −1 and high thermal stability (300 °C). The adsorption capacity of these polyaminals was determined over different toxic metals such as Cr(VI), Cu(II), Cd (II) and Pb(II) at different pH. The results showed greater chromium adsorption capacity in acid medium (pH 2), while the divalent cations were mainly adsorbed at pH 5. MA-Py that displayed the highest nitrogen content (37%) and highest specific surface area (424 m 2 g −1 ) also showed the highest adsorption capacities of this series, with values of 27.22, 26.42, and 53.13 mg/g for Cr(VI), Cd(II) and Pb(II); respectively. Additionally, MA-Py and MA-iPh with adsorption capacities of 29.12 and 25.02 mgg −1 for Cr(VI) and Cd(II), were competitive in terms of adsorption capacities regarding commercial ion exchange-resins which shown adsorptions in the range 13.7–21.3 mg/g.